Comprehensive Study of Archaeozoological Materials of the Settlement of the Srubnaya Culture «Staryye Chuti Campsite» - Natalya V. Roslyakova; Olga P. Bachura; Alexey I. Zhemkov; Igor V. Askeyev; Dilyara N. Shaymuratova (Археология евразийских степей)
The article presents the description of archaeozoological study of animal bones from the Staryye Chuti campsite of the Srubnaya culture on the Ik River. An osteological collection with more than 3000 bones was investigated. There are different categories of bone remains by their origin: kitchen garbage, remnants of craft and ritual complexes. In collection there are bones of all domestic ungulates species, dogs, foxes, beavers, birds, and fish, as well as mollusk shells. The kitchen remnants are significantly dominated by bones of cattle, whose meat constituted the major part of the meat diet of the settlement inhabitants. Horse meat, mutton, goat meat and pork were eaten in much smaller quantities. For large domestic ungulates and small cattle the several forms of exploitation have been established. Slaughtering of livestock at the settlement was carried out all year round. There was no selectivity of particular species slaughtering during certain season of the year. Hunting of wild mammals and birds and fishing played an insignificant role in economic activity. A detailed study of animal bone sets from filling and bottom of wells allows us to assume the connection of them with sacrificial complexes. The main parameters of the collection are similar to the ones from synchronous settlement of Eastern Europe, for which the mobile form of cattle breeding has been reconstructed.